Analisa Pengaruh Perubahan Penggunaan Lahan terhadap DAS Batang Kuranji dengan Menggunakan Model Soil and Water Assessment Tool (SWAT) - Annisa Fitriana Definnas; Rozy Fairuzza Reyandal; Elvi Roza Syofyan; Wisafri - - (Jurnal Ilmiah Poli Rekayasa, 2020)
Batang Kuranji is one of six rivers that flow in the city of Padang, and is the main source of water for residents of Padang City to meet the raw water which is then processed into clean water and the needs of Mt. Nago irrigation water. The increase in population causes the population to move to a higher area (green zone). Batang Kuranji watershed has experienced a reduction in the area of forest land due to changes in land use activities by the population movement. As a result, land that was not watertight at first became watertight, the mainstay discharge or expected discharge is always available, always increasing during the rainy season and decreasing during the dry season. This study was conducted to determine the extent of land use change in the Batang Kuranji watershed, also to determine the main discharge that occurred in 2009, 2011, and 2017 using the Soil and Water Assessment Tool (SWAT) model. The analysis consists of four processes, namely watershed delineation, formation of a Hydrologic Response Unit (HRU), formation of climatological data, and finally the simulation process. HRU analysis results obtained by Batang Kuranji watershed into 9 sub-watersheds, the dominant HRU is protection forest by 62%, soil type with depth (solum) level A and B, runoff coefficient of 0.3 and NS value obtained by 0.6. This shows that the SWAT model can predict the hydrological process in the upstream Batang Kuranji watershed. The most influential land use on surface runoff is land use for settlement.